The Role of Teacher Attributes in Overcoming Supervision Constraints Education - Azhari, Ana Kurnia; Santoso, Budi; Rofiq, Ainur (Aksara Shofa, 2024)
This study aims to analyze the role of teacher traits in overcoming obstacles to educational supervision in order to improve the quality of education at SMA Alhikmah Muncar Banyuwangi. Using a qualitative approach with a descriptive type, this study involved in-depth interviews, participatory observation and document analysis as data collection techniques. Informants were purposively selected to gain in-depth insight into the experiences of teachers, supervisors and students. The results show that teacher traits such as openness, empathy, assertiveness and creativity significantly contribute to overcoming supervision obstacles, as well as creating a positive learning environment and supporting improved student learning outcomes. The implication of this study is the importance of developing positive traits in teachers through training and professional development, which can be an effective strategy in improving the quality of education. This study also contributes to the understanding of the dynamics of the relationship between teacher traits and the effectiveness of educational supervision in the context of secondary schools.